Transport and ICT sectors in Finnish development cooperation - Rankamo, Oskari (fi=Turun yliopisto|en=University of Turku|, 2017)
any western economies are facing budget cuts and the funds indicated for development cooperation have been under public scrutiny. This has led to debate that country´s development cooperation should provide more opportunities for donor´s private sector while carrying out more traditional development objectives. The purpose of this thesis is to analyze private sector involvement in Finnish development cooperation´s transport and ICT sectors from donor country perspective. The study is conducted as a qualitative research. The analytical framework is focused on the nature of transport and ICT projects in general and mechanisms, roles and operators of the projects in these sectors. Additionally transport and ICT capabilities and needs in developing countries and role of transport and ICT investments for economic and social development are explored. The empirical data meanwhile is constructed from Finnish expert interviews as primary source and evaluation reports of development cooperation as a secondary source. The interviews are concluded as theme interviews, which enables flexible and dialogical discussion. Empirical research contains also chapter for Dutch and Danish development cooperation in transport and ICT sectors as Finnish cooperation and private sector participation were compared to these European comparison countries. The findings of this study indicate that Finnish development cooperation is not extensive on transport and ICT sectors and the objectives for Finnish private sector participation in the development policies of the Ministry for Foreign Affairs of Finland are basically none. The promotion of Finnish private sectors is mostly directed to national agencies such as Finnpartnership, Finnfund and Finpro. These are funded totally or partly by government funding. Finland seems to lag behind Dutch and Danish on how donor country private sector participation is being viewed as a fundamental part of the development policy itself. Finnish development cooperation seems to be heading to the direction were even more multilateral aid is being promoted and this could signify lesser influencing opportunities for the small country such as Finland. The study though suggests that there would be significant need and opportunities for Finnish expertise in transport and ICT sectors in developing countries.